2006
DOI: 10.1017/s0022112006001467
|View full text |Cite
|
Sign up to set email alerts
|

Roughness effects in turbulent pipe flow

Abstract: Mean flow measurements are presented for fully developed turbulent pipe flow over a Reynolds number range of $57\,{\times}\,10^3$ to $21\,{\times}\,10^6$ where the flow exhibits hydraulically smooth, transitionally rough, and fully rough behaviours. The surface of the pipe was prepared with a honing tool, typical of many engineering applications, achieving a ratio of characteristic roughness height to pipe diameter of 1 : 17000. Results for the friction factor show that in the transitionally rough regime this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
113
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(131 citation statements)
references
References 17 publications
14
113
2
Order By: Relevance
“…Experiments on honed roughness carried out by Shockling et al (2006) and Schultz & Flack (2007), and grit-blasted surfaces studied by Flack et al (2016) also showed similar trends to those of Nikuradse (1933) over the Reynolds number range, consistent with the present results. However, this tends to contradict the observation of Bradshaw (2000), who suggested that realistic roughness should exhibit more Colebrook-type than Nikuradse-type behaviour due to the large range of length scales present compared with Nikuradse's sand grains.…”
Section: Roughness Functionsupporting
confidence: 90%
See 2 more Smart Citations
“…Experiments on honed roughness carried out by Shockling et al (2006) and Schultz & Flack (2007), and grit-blasted surfaces studied by Flack et al (2016) also showed similar trends to those of Nikuradse (1933) over the Reynolds number range, consistent with the present results. However, this tends to contradict the observation of Bradshaw (2000), who suggested that realistic roughness should exhibit more Colebrook-type than Nikuradse-type behaviour due to the large range of length scales present compared with Nikuradse's sand grains.…”
Section: Roughness Functionsupporting
confidence: 90%
“…In particular, the honed pipe roughness of Shockling et al (2006) did not exhibit as pronounced an inflectional behaviour as shown by the data of Nikuradse (1933) or Ligrani & Moffat (1986), and reached the fully rough regime at comparatively lower k …”
Section: Roughness Functionsupporting
confidence: 51%
See 1 more Smart Citation
“…It has long been accepted that inner scaling fails for higher-order statistics near the wall even for the case of smooth walls, though there are many examples demonstrating that the mean velocity is self-similar; see, for example, the reviews by Raupach, Antonia & Rajagopalan (1991) and Jiménez (2004), as well as the more recent results of Shockling, Allen & Smits (2006) and . Townsend (1961) explained this discrepancy by introducing the concept of 'inactive' motion (see also Bradshaw 1967;Morrison, Subramanian & Bradshaw 1992), in which the 'top-down' effect (Hunt & Morrison 2000) of the large-scale, non-shear-stress-bearing motion near the wall is assumed to be a low-frequency modulation of the shear-stressbearing, active motion by the low-wavenumber wall-parallel velocity components.…”
Section: Introductionmentioning
confidence: 99%
“…Friction along the solid-liquid interface tends to increase with increasing surface roughness and interface instabilities [100]. It is the primary cause of energy losses and thus, of the flow capacity reduction within pipelines [17].…”
Section: Operational Problemsmentioning
confidence: 99%